PELATIHAN PPGD PADA KINERJA PERAWAT DI IGD DAN ICU RSUD AHMAD YANI METRO - Heru Supriyatno; Pira Prahmawati; Pilipus Benitius A.S (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
One of nurses in the hospital is handling emergency cases. The minimum ability of emergency nurse services in Indonesia based on the Ministry of Helath’s work guidelines is to open and clear the airway, clean pulmonary ventilation and oxygenation (breathing), provide cardiopulmonary resuscitation, provide bleeding and bandage a splint. Not all emergency services have valid certificates. Not all emergency services have valid certificate, whereas in the IGD Key Performance Indicator (KPI) standard, all emergency service providers must have a valid certificate (ATLS/BTLS/ACLS/PPGD). This makes the quality of the health personnel who work, especially emergency nurses, less maintained, so that not all customers are satisfied, even though in the IGD KPI standard 100% of customers must be satisfied with the services provided. The nurse’s performance can be seen from the indicators of patient mortality and the ability to handle life saving cases from patients. The purposes of this study was to expalin the relationship between PPGD training and the performance of nurses in the IGD and ICU at RSUD Ahmad Yani Metro. The research design used is the cross sectiona approach and the results of the Chi Square test obtained a P – Value of 0.004, meaning that there is the relations between PPGD training program and the nurse’s performance with an OR value of 13.571.